Tingkat Kecemasan, Stres, dan Depresi pada Wanita yang Menjalani Program In Vitro Fertilization (IVF) - Kurniawati, Erna Yovi; Devaisnaini, Arsita Rahma (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to describe the level of anxiety, stress, and depression in women undergoing In Vitro Fertilization (IVF) program and to see the distribution of psychological disorders based on sociodemographic characteristics and the stage of IVF program undertaken. The design of this study was descriptive quantitative with purposive sampling technique on 28 women who were undergoing IVF cycles in infertility clinics in Yogyakarta Special Region. Data were collected online through a questionnaire containing Hamilton Anxiety Rating Scale (HARS), Perceived Stress Scale (PSS), and Beck Depression Inventory-II (BDI-II) instruments. Descriptive analysis showed that most respondents experienced moderate anxiety (42%), mild stress (38%), and mild depression (36%). The analysis also showed that sociodemographic characteristics, such as age older than 35 years, non-working employment status, and low education, had a higher tendency towards psychological disorders. In addition, certain phases of IVF, such as the waiting phase after embryo transfer, appeared to be associated with increased levels of anxiety and stress. This study emphasizes the importance of more intensive psychological support, especially for women who are in the more stressful stages of IVF, as well as for those with sociodemographic risk factors that increase their vulnerability to psychological disorders.